Early postoperative versus delayed radiotherapy in bladder sparring treatment of patients with high-grade urinary bladder cancer - P. G. Yakovlev (Клінічна хірургія)
Objective. To study the prevalence and effect on the survival of high grade bladder cancer (G3 UBC) patients of external beam radiotherapy delivered in early or delayed period after the bladder preserving surgery.